HAMBA TUHAN DAN SENI MEMBERI - Anton Siswanto (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract God's servant is identical to the example in expressing Christ's love for the congregation and being a public figure in all thoughts, words and actions. In this paper, a Biblical Principle is explained, which is love exhibited by